Symptom provocation for treatment of obsessive-compulsive disorder using transcranial magnetic stimulation: A step-by-step guide for professional training - Maia, Ana; Almeida, Sílvia; Cotovio, Gonçalo; Rodrigues da Silva, Daniel; Viana, Francisco Faro; Grácio, Jaime; Oliveira-Maia, Albino J. (Frontiers in Psychiatry, 2022)
Transcranial Magnetic Stimulation (TMS) is a non-invasive brain stimulation technique that was cleared by the Food and Drug Administration (FDA) for the treatment of Obsessive-Compulsive Disorder (OCD) in 2018. The approved protocol includes individualized symptom provocation before each stimulation session, to elicit a moderate level of obsessional distress. Although symptom provocation can be a delicate, demanding, and uncomfortable procedure, structured training methods for those who are going to apply it are not available. Here, we describe a model for training in symptom provocation for TMS technicians, developed at the Champalimaud Clinical Center in Lisbon, Portugal. Our programme includes two-sessions dedicated to clinical communication and symptom provocation techniques from a theoretical and practical perspective. Additionally, supervision meetings are conducted during treatment of patients, allowing regular case discussion and redefinition of symptom provocation hierarchy, as needed. In addition to having a strong practical component, our training program is short and pragmatic, allowing for easy implementation and fluid transition to clinical practice. By sharing our experience, we hope to contribute to systematize training procedures required for symptom provocation in the context of TMS, and to qualitatively describe a methodology that can be used for implementation of TMS programmes for the treatment of OCD.